Consistency checking in multiple UML state diagrams using super state analysis - Alanazi, Mohammad N. (Kansas State University, 2008)
The Unified Modeling Language (UML) has been designed to be a full standard notation for Object-Oriented Modeling. UML 2.0 consists of thirteen types of diagrams: class, composite structure, component, deployment, object, package, activity, use case, state, sequence, communication, interaction overview, and timing. Each one is dedicated to a different design aspect. This variety of diagrams, which overlap with respect to the information depicted in each, can leave the overall system design specification in an inconsistent state. This dissertation presents Super State Analysis (SSA) for analyzing UML multiple state and sequence diagrams to detect the inconsistencies. SSA model uses a transition set that captures relationship information that is not specifiable in UML diagrams. The SSA model uses the transition set to link transitions of multiple state diagrams together. The analysis generates three different sets automatically. These generated sets are compared to the provided sets to detect the inconsistencies. Because Super State Analysis considers multiple UML state diagrams, it discovers inconsistencies that cannot be discovered when considering only a single UML state diagram. Super State Analysis identifies five types of inconsistencies: valid super states, invalid super states, valid single step transitions, invalid single step transitions, and invalid sequences.
Keywords: Software engineering; Modeling languages; UML; Software models; State diagrams; Sequence diagrams; Computer Science (0984)